Effect of gender on salivary immunoglobulin and complements in autism children - Suha Talal Abd; Wasan Lafta Abdulla; Muna Abdulla Saleem; Shaimaa Sabte Mutlak; Zahraa Tariq Hasson (Medical Journal of Babylon, 2023)
Background: Autistic spectrum disorder (ASD) is considered a disease of neurological development; until now, there are no specific tests or biological indicators that may be utilized to establish the diagnosis. A delay in ASD diagnosis delays the initiation of pharmacological and therapeutic interventions, preventing biopsychosocial development and lowering the individual’s prognosis. Objectives: This study aimed to find a correlation between ASD and gender effect for some salivary immunoglobulin (Ig) and complements to facilitate the diagnosis ASD. Materials and Methods: It involved 30 child diagnosed with autism, aged 6- to 12-year-old. Those children were represented all ASD children of both sexes who satisfied the criteria of diagnosis for autism, saliva samples were collected and enzyme-linked immunosorbent assay kit was used to measure C3, C4, IgA, and IgG. Results: The result shows a significant increase in the concentration of IgG in male children as compared to female children, in spite of higher level of the rest variables for the male children with ASD. Conclusion: There was an effect of gender on salivary Ig in patient with ASD.